The Bedford-Row Conspiracy - Thackeray, William Makepeace, 1811-1863 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Bedford-Row Conspiracy" by William Makepeace Thackeray is a novel written during the mid-19th century. The story revolves around the lives and romantic entanglements of its characters, primarily focusing on John Perkins, a young barrister, and Lucy Gorgon, along with their respective families, set against the backdrop of political and social rivalries in the fictional town of Oldborough. The opening of the novel introduces us to the whimsical and romantic deliberations between John Perkins and Lucy Gorgon, who are planning their future together while navigating the expectations of their families. This initial conversation hints at both the lighthearted and serious themes of love and social class that will permeate the narrative. As details of their backgrounds unfold, we learn about the contrasting fortunes and standing of their relatives, particularly the domineering Lady Gorgon and the ambitious attorney William Pitt Scully. The chapter effectively sets the stage for the ensuing conflicts, including romantic rivalries and political machinations that arise within the social fabric they inhabit. (This is an automatically generated summary.)
Release date is 1999-12-01
Produced by Les Bowler, and David Widger
Keywords: England -- Social life and customs -- 19th century -- Fiction